Maternal genetic history of southern East Asians over the past 12, 000 years. (20th October 2021) - Liu, Yalin; Wang, Tianyi; Wu, Xichao; Fan, Xuechun; Wang, Wei; Xie, Guangmao; Li, Zhen; Yang, Qingping; Cao, Peng; Yang, Ruowei; Liu, Feng; Dai, Qingyan; et al.
Abstract: Southern East Asia, including Guangxi and Fujian provinces in China, is home to diverse ethnic groups, languages, and cultures. Previous studies suggest a high complexity regarding population dynamics and the history of southern East Asians. However, large-scale genetic studies on ancient populations in this region are hindered by limited sample preservation. Here, using highly efficient DNA capture techniques, we obtain 48 complete mitochondrial genomes of individuals from Guangxi and Fujian in China and reconstruct their maternal genetic history over the past 12, 000 years. We find a strong connection between southern East Asians dating to ~12, 000–6000 years ago and present-day Southeast Asians. In addition, stronger genetic affinities to northern East Asians are observed in historical southern East Asians than Neolithic southern East Asians, suggesting increased interactions between northern and southern East Asians over time. Overall, we reveal dynamic connections between ancient southern East Asians and populations located in surrounding regions, as well as a shift in maternal genetic structure within the populations over time.